1995
DOI: 10.1295/polymj.27.664
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermotropic Properties of Polyurethanes Prepared from 2,5-Tolylene Diisocyanate and 2,6-Bis(ω-hydroxyalkoxy)naphthalenes

Abstract: ABSTRACT:A series of thermotropic polyurethanes containing no mesogenic unit were synthesized by polyaddition of a para-type diisocyanate such as 2,5-tolylene diisocyanate (2,5-TDI) with 2,6-bis(w-hydroxyalkoxy)naphthalenes (BHNm: HO(CH2)mOC10H 6 O(CH2)mOH; m is the carbon number in the hydroxyalkoxy group). Intrinsic viscosities of the polymers were in the range of 0.27---0.48 dL g-1 . The thermal properties of these polymers were studied by differential scanning calorimetry, thermogravimetric analysis, polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In the copolyurethanes containing both meta and para units in random distribution, the decrease in regularity of distributions of the mesogenic units and urethane linkages in the polymer backbone must have caused the decrease in persistence length and effective axial ratio, resulting in the decrease in both mesogenic interactions and intermolecular hydrogen bondings. Thereby, an appropriate magnitude of the intermolecular interactions to cause the enantiotropic liquid crystallinity might be attained, because in the para-type polyurethanes containing biphenylene mesogen, strong intermolecular interactions readily caused the crystallization but not the liquid crystallization. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the copolyurethanes containing both meta and para units in random distribution, the decrease in regularity of distributions of the mesogenic units and urethane linkages in the polymer backbone must have caused the decrease in persistence length and effective axial ratio, resulting in the decrease in both mesogenic interactions and intermolecular hydrogen bondings. Thereby, an appropriate magnitude of the intermolecular interactions to cause the enantiotropic liquid crystallinity might be attained, because in the para-type polyurethanes containing biphenylene mesogen, strong intermolecular interactions readily caused the crystallization but not the liquid crystallization. …”
Section: Resultsmentioning
confidence: 99%
“…We have been studying the synthesis of thermotropic para-type aromatic polyurethanes containing alkylene spacers. The para-type polyurethanes had a tendency to readily crystallize both by mesogenic interactions and by the intermolecular hydrogen bondings. Thus, first, to examine the effects of the mesogenic interactions, para-type polyurethanes without any mesogen were prepared. , Those polyurethanes exhibited monotropic liquid crystallinity induced by the intermolecular hydrogen bondings alone. Next, to decrease the intermolecular hydrogen bondings, para-type mesogen-containing copolyurethanes including two alkylene spacers with different lengths were synthesized .…”
Section: Introductionmentioning
confidence: 99%
“…Uryu et a1. 21,22) also reported that semirigid polyurethanes composed of non-mesogenic units exhibit thermotropic LC properties due to intermolecular interaction via hydrogen bonding of urethane linkages. These results suggest that the amide or urethane linkage plays an important role in LC formation and the traditional biphenyl or diphenyl units are not always necessary to form LC phases when a certain interaction occurs between the polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…5 properties was discussed. [10][11][12][13][14][15][16][17] Some of them In the present paper, this reaction was applied showed unstable and/or ill-defined LC textures in to the synthesis of novel fluorine-containing therspite of the presence of the urethane linkage, motropic semirigid LC copolyurethanes from the which promotes LC formation via intermolecular monomers 1 and 2a,b and alkylene diphenyl dihydrogen bonding, 10-14 in the backbone. The incarbamates 3a-i (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%